Kretek Museum and Preservation of Historical Heritage of the Kudus Kretek Cigarette Industry 1986-2010 as a Source for Learning History - Pratama, Rifki Yoga (Indonesian Journal of History Education, 2017)
This article aims (1) to determine the role of museums in preserving the setting of the heritage cigarette industry, (2). To find a clove museum under the management of PPRK, (3). To find a clove museum under the management of the Holy Disbudpar. The benefits that can be obtained from this study are increasing knowledge for the reader on the history of past Cigarettes in the Dutch East Indies until this era and growing understanding of the Holy Kretek Museum. The method used is historical research that includes four stages: heuristic, source criticism, interpretation, and historiography. The spatial scope of this research is the Getas Village Housing Jati subdistrict, while the temporal scope of the authors takes the years 1986-2010. It can be concluded that the Kretek Museum was built to emphasize the Holy City as the City of Kretek. Kretek Museum presents a collection of objects relating to the development of cigarette companies.